Chlorophyll fluorescence as a tool for management of plant resources - Méthy, M; Olioso, A; Trabaud, L (Remote Sensing of Environment, 1994)
Light-induced chlorophyll fluorescence has become a tool which has ever-increasing potential application to experimental plant physiology. The effects of frost, heat, and drought have been analyzed using the kinetics of individual leaves of two representative types of life form: an evergreen tree (holm oak) dominant in the Mediterranean Basin and an annual cultivated legume (soybean). Various indices were used to quantify their response to environmental stress. Canopy fluorescence for the two types of plants was simulated. For two levels of measurement, leaf or canopy, light-induced fluorescence appears to be helpful for forest or crop management in the Mediterranean area.
Keywords: chlorophyll fluorescence induction; crop management (PG); environmental stress; Forest management